Cryogel‐based Injectable 3D Microcarrier Co‐culture for Support of Hematopoietic Progenitor Niches. Issue 11 (23rd November 2021) - Tavakol, Daniel Naveed; Bonini, Fabien; Tratwal, Josefine; Genta, Martina; Brefie‐Guth, Joé; Braschler, Thomas; Naveiras, Olaia
Abstract: Although hematopoietic stem cell (HSC) transplantation can restore functional hematopoiesis upon immune or chemotherapy‐induced bone marrow failure, complications often arise during recovery, leading to up to 25% transplant‐related mortality in treated patients. In hematopoietic homeostasis and regeneration, HSCs in the bone marrow give rise to the entirety of cellular blood components. One of the challenges in studying hematopoiesis is the ability to successfully mimic the relationship between the stroma and hematopoietic stem and progenitor cells (HSPCs). This study and the described protocols propose an advantageous method for culturing and assessing stromal hematopoietic support in three dimensions, representing a simplified in vitro model of the bone marrow niche that can be transplanted in vivo by injection. By co‐culturing OP9 bone marrow–derived stromal cells (BMSCs) and cKit + Sca‐1 + Lin – (KLS + ) HSPCs on collagen‐coated carboxymethylcellulose scaffolds for 2 weeks in the absence of cytokines, we established a methodology for in vivo subcutaneous transplantation. With this model we were able to detect early signs of extramedullary hematopoiesis. This work can be useful for studying various stromal cell populations in co‐culture, as well as simple transfer by injection of these scaffolds in vivo for heterotopic regeneration of the marrow microenvironment. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 17, 2022, after first online publication: CSAL funding statement has been added.] Basic Protocol 1 : Isolation of HSPCs from mice Basic Protocol 2 : Co‐seeding of HSPCs and BMSCs on collagen‐coated CCMs Basic Protocol 3 : Maintenance, real‐time imaging, and analysis of co‐seeded scaffolds Basic Protocol 4 : End‐point analysis of co‐seeded scaffolds using flow cytometry and CFU assays Basic Protocol 5 : Transplantation of scaffolds by subcutaneous injection Support Protocol : Preparation of custom scaffold drying device